Research Themes for Events - Finkel, Rebecca (CABI, 2014)
When conceptualizing this book, the editors made a point to identify the key themes of the prevailing research literature in events and recognized the need to highlight the seminal literature and theoretical frameworks under- pinning primary research in this growing subject area (e.g. Richards and Palmer, 2010; Foley et al., 2011; Getz, 2012). Broadly, this is an events management book framed in a research context drawing social scientiﬁ c approaches. It dif ers from other subject-speciﬁ c books by not focusing on operations or manage- ment but rather on theoretical frameworks illustrated through case studies. The goal is to shine a brighter spotlight on research, bringing it to the forefront of the discussion in the events management ﬁ eld. This is neither a research methods text nor a business text but rather a text for the events researcher to use as a guide for comprehending what are the particular challenges of conducting primary research in this ﬁ eld. As events research encompasses cross-disciplinary perspectives, drawing from tourism, leisure, cultural studies, urban geography, sociology, marketing and other social science and management discourses, not all of the divergent themes that events researchers pursue could be included. The editors, therefore, purposefully selected the themes for this book to present a consistency and coherence that many edited books lack.